Characterization of Polyvinylidene Fluoride (PVDF) Electrospun Fibers Doped by Carbon Flakes - Kaspar, Pavel; Sobola, Dinara; Částková, Klára; Knápek, Alexandr; Burda, Daniel; Orudzhev, Farid; Dallaev, Rashid; Tofel, Pavel; Trčka, Tomáš; Grmela, Lubomír; Hadaš, Zdeněk (Polymers, 2020)
Polyvinylidene fluoride (PVDF) is a modern polymer material used in a wide variety of ways. Thanks to its excellent resistance to chemical or thermal degradation and low reactivity, it finds use in biology, chemistry, and electronics as well. By enriching the polymer with an easily accessible and cheap variant of graphite, it is possible to affect the ratio of crystalline phases. A correlation between the ratios of crystalline phases and different properties, like dielectric constant as well as piezo- and triboelectric properties, has been found, but the relationship between them is highly complex. These changes have been observed by a number of methods from structural, chemical and electrical points of view. Results of these methods have been documented to create a basis for further research and experimentation on the usability of this combined material in more complex structures and devices.
Keywords: Fourier-transform infrared spectroscopy; scanning electron microscopy; triboelectric effect; Raman spectroscopy; graphite; polyvinylidene fluoride; X-ray diffraction